Small Firm Owner-Managers’ Networks In Tourism And Hospitality - Ghazali, Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Firms participate in network relationships with others to reap the resources that are unavailable within. The resources may consist of goods, services, information, advice or support. The flow of resources into the firm has the potential enhance the capability of a firm to react to the external competitive environment. Generally network relationships can be formal and/or informal. For a small firm, a network is more likely to be informal and have social links to individuals such as family, friends and acquaintances. This paper investigates the network features and networking activities of the small tourism and hospitality owner-managers. The context of the research is the owner-managers of chalet accommodation firms located at the coastal and island destinations in the east of Peninsular Malaysia. The networks are composed of family and ethnic linkages and mainly bounded by specific locality like the ‘village’. Informal ties are with those with a common interest in tourism product and services within a destination. The networks contacts for business and social purposes are consisting the same people. Chalet owner-managers attached to family for financial and friends for other matters throughout the business life. This was due to the trust that built through the years of relationships with the strong ties. Furthermore, the main reason for networking with the contacts was for exchange of ideas, advice, and help. The owner-managers found that the networks did not generate tangible benefits, however were strong in knowledge sharing.